Komunikasi Politik Gerakan #2019GantiPresiden - Sujoko, Anang (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2019)
In the 2019 general election, social media became an important part in building a political image as well as a channel for political communication. One of the opposition movements against the incumbent was the #2019GantiPresiden movement. The movement was a channel of political communication for people who personally wanted to have a new president. This study aimed to reveal how the #2019GantiPresiden political communication movement during 2018 and the repressive treatment experienced by them. This study used a qualitative research method of text analysis of several online media such as Twitter and micro-blogging. The results showed that the #2019GantiPresiden movement was an organic and voluntary based political communication movement. The spread of this movement was increasingly massive with the support of social media in the form of Twitter in building mass political support.